Pediatric Posterior Cruciate Ligament Avulsion Fracture of the Tibial Insertion: Case Report and Review of the Literature - Hurni, Yannick; De Rosa, Vincenzo; Gonzalez, Jorge Gabriel; Mendoza-Sagaon, Mario; Hamitaga, Flurim; Pellanda, Giorgia (The Surgery Journal, 2017)
Background Posterior cruciate ligament (PCL) avulsion fracture of the tibial insertion is a very rare injury in children. In addition to performing an attentive clinical examination, radiologic studies are fundamental for its correct diagnosis and treatment. Its management may be either conservative or operative. So far, only a few cases treated conservatively have been reported in the pediatric population, with controversial results.Methods We prospectively collected and reviewed clinical and radiographic data of an 11-year-old boy with avulsion fracture of the tibial insertion of the PCL. In addition, we performed a systematic review of the literature available to date.Results We decided to treat the avulsion fracture in a conservative way. The patient has been followed with accurate clinical and radiological follow-up controls until complete recovery.Conclusion Posterior cruciate avulsion fracture is a very rare finding in children, and no definitive indications for its appropriate management exist. With this report, we demonstrate that these fractures can be treated conservatively in selected cases with good results, avoiding potential surgical-related complications.Study Design This is a case report (level of evidence V).
Keywords: posterior cruciate ligament; avulsion fracture; pediatric